The Evaluation Of The Prospect Series In Terms Of Vocabulary As The English Material Of Iran's Junior High School - Hassanpour, Milad; EftekhariMannesh, Majid (International Journal of Psychosocial Rehabilitation, 2024)
Undoubtedly, investigating the frequency of words in Prospect series can lead to improvement ofstudents in order to shed light on the evaluation of teaching materials in the context of Iran. It isneeded to investigate the frequency of the words of Prospect series. Using the most frequentwords can enhance the efficiency of students’ English vocabulary knowledge. The present studyaimed at finding out the frequency of words of Prospect series as part of the Iranian junior highschool. To this end, the words of Prospect series were gathered. Since, this study sought forevaluation of word frequency of vocabulary, another material was needed. Therefore, COCAonline website was used. After finding their frequency, the most and the least frequent words,they were put into several tables. Based on word frequency analysis, words chosen for Prospectseries are not the most frequent words for junior high school students. Therefore, the nullhypothesis could be proved that the words chosen for Prospect series are not the most frequentwords in English language for junior high school students in Iran. According to the result of thepresent study, the word selection of high school English materials is not useful enough thereforeit needs revision. Finally, it can be concluded from the result of the present study, there should bemore focus on material evaluation in particular English materials which have been used in juniorhigh school level in Iran to compensate the recent shortages in terms of word selection.